The Role of Spirituality in Shaping Social Interaction in Kendari City: A Study of the Meaning of Worship in Community Life - Muallimah, Muallimah; Asman, Asman; Arsam, Arsam (Universitas Muhammadiyah Magelang, 2024)
The spiritual aspect plays an important role in building social interaction in community groups. This paper aims to understand and analyze the social interaction of the people of Kendari city in the context of worship affecting the behavior of individuals and communities in social interaction. The data was collected from interviews, with a qualitative method of phenomenological approach. The mapping of individual or group behavior was confirmed to community groups as participants in this study. The results of the study demonstrate that the role of spirituality by exploring the meaning of worship led to a new concept that worship is able to raise spiritual values such as morality, unity, affection, and awareness that have implications for people's lives. This study offers Kendari City residents a fresh perspective on how these spiritual principles might serve as a guide in daily life. In line with that, this paper suggests the need for institutional involvement and all elements of society to solve the problem of religious understanding using a spiritual value approach rather than a bureaucratic one.